2012
DOI: 10.1016/j.socscimed.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Feeding her children, but risking her health: The intersection of gender, household food insecurity and obesity

Abstract: This paper investigates one explanation for the consistent observation of a strong, negative correlation in the United States between income and obesity among women, but not men. We argue that a key factor is the gendered expectation that mothers are responsible for feeding their children. When income is limited and households face food shortages, we predict that an enactment of these gendered norms places mothers at greater risk for obesity relative to child-free women and all men. We adopt an indirect approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
140
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 51 publications
7
140
1
2
Order By: Relevance
“…Women with children present higher overweight and obesity rates in FI situations, in comparison with women without children and with men 30 . Although the present study did not identify the presence and number of children, the Brazilian Demographic Census carried out in 2010 indicated that low-income women have a greater number of children than those in higher income groups 33 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Women with children present higher overweight and obesity rates in FI situations, in comparison with women without children and with men 30 . Although the present study did not identify the presence and number of children, the Brazilian Demographic Census carried out in 2010 indicated that low-income women have a greater number of children than those in higher income groups 33 .…”
Section: Discussionmentioning
confidence: 88%
“…Among women in developing countries, several studies have indicated a relationship between moderate levels of FI and overweight 10,30 . In Brazil, according to the National Demographics and Health Survey of 2006 31,32 , within the research group of Demographic Health Surveys (DHSs), there were associations between moderate FI and obesity among women 14 and between severe FI and obesity among female adolescents 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not locate any studies linking depth of poverty and gender with food insecurity in marginally housed populations specifically, this dynamic is consistent with trends noted in the general population (46) . Studies conducted among North American families have shown that food insecurity tends to be higher among women, who may make sacrifices to try to buffer children and other family members from experiencing food insecurity (47)(48)(49) . It is difficult to know if this explanation applies to our finding, as SRO buildings house single adults and generally do not allow children to live on the premises.…”
Section: Discussionmentioning
confidence: 99%
“…Research concerning obesity as it relates to women on low income is particularly important given the inverse correlation between income level and obesity in women (PHAC, 2011;Martin and Lippert, 2012) -and the tendency to place blame on women for this situation instead of working towards a more nuanced understanding of the factors that might contribute to this trend. Very little sociocultural research has applied qualitative methodologies to focus on contextual factors influencing the uptake of health practices related to body weight for underprivileged women.…”
Section: Women Lifestyle and Obesity A Critical Approachmentioning
confidence: 99%